2005
DOI: 10.1158/0008-5472.can-05-1783
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA Gene Expression Deregulation in Human Breast Cancer

Abstract: MicroRNAs (miRNAs) are a class of small noncoding RNAs that control gene expression by targeting mRNAs and triggering either translation repression or RNA degradation. Their aberrant expression may be involved in human diseases, including cancer. Indeed, miRNA aberrant expression has been previously found in human chronic lymphocytic leukemias, where miRNA signatures were associated with specific clinicobiological features. Here, we show that, compared with normal breast tissue, miRNAs are also aberrantly expr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

128
2,960
7
56

Year Published

2007
2007
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 3,689 publications
(3,175 citation statements)
references
References 23 publications
128
2,960
7
56
Order By: Relevance
“…Additionally, a significant number of microRNAs are encoded within fragile sites, regions of amplification, or common breakpoint regions associated with human cancers. [6][7][8][9][10][11][12] Regulatory Mechanisms of microRNA Expression: the Role of Hypoxia…”
Section: Small Size Regulators With Far-reaching Impactmentioning
confidence: 99%
“…Additionally, a significant number of microRNAs are encoded within fragile sites, regions of amplification, or common breakpoint regions associated with human cancers. [6][7][8][9][10][11][12] Regulatory Mechanisms of microRNA Expression: the Role of Hypoxia…”
Section: Small Size Regulators With Far-reaching Impactmentioning
confidence: 99%
“…With the development of comprehensive treatment of breast neoplasms, the mortality rate has been significantly reduced. Researchers have found that many miRNAs are associated with breast neoplasms by clinical experiments, such as mir‐155 and mir‐21 6. We used our method to predict the candidate miRNAs for breast neoplasms, and we listed the top 50 predicted candidate miRNAs (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…In a study regarding breast cancer, lorio et al [62] found that the miRNA expression patterns were significantly different between normal and neoplastic breast tissues, with miR-125b, miR-145, miR-21, and miR-155 significantly reduced in breast cancer tissues. They also observed that the expression of miRNAs was correlated with specific breast cancer clinicopathologic features, such as tumor stage, proliferation index, estrogen and progesterone receptor expression, and vascular invasion[62].…”
Section: Mirna and Cancermentioning
confidence: 99%